2009
DOI: 10.1159/000243725
|View full text |Cite
|
Sign up to set email alerts
|

Effect of <i>L</i>-Asparaginase Combined with Vincristine and Prednisolone on Acute Myeloblastic Leukemia (M0) Associated with Non-Hodgkin Lymphoma

Abstract: A 66-year-old Japanese woman was referred to us because of severe anemia and fever and presented at our hospital. She was eventually diagnosed as having acute myeloblastic leukemia (AML; M0) with non-Hodgkin lymphoma (NHL). We investigated the therapeutic efficacy of L-asparaginase (L-Asp), vincristine and prednisolone for both her AML and NHL. Asparagine synthetase (AS) activity in her AML blast cells was undetectable. A lymph node biopsy specimen revealed NHL of the marginal zone B cell type. Complete remiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…A more complete attempt to categorize AML subgroups on the basis of ASNase sensitivity indicated that M1 and M0 were the most sensitive, while M3 and M7 were poorly sensitive and M4-M5 were confirmed to have a moderate sensitivity (35). Although no correlation was made between ASNase sensitivity and ASNS protein expression in that paper, a good response to therapy associated with low ASNS mRNA expression was later reported, at least for M0 (36). More recently, since chromosome 7 monosomy (-7) is frequently detected in adverse-risk AML and therapy-related myeloid neoplasms in children, the hypothesis that this aberration correlates with sensitivity to ASNase was investigated (37).…”
Section: Low Expression Of Asns As a Marker Of Sensitivity To Asnase mentioning
confidence: 95%
“…A more complete attempt to categorize AML subgroups on the basis of ASNase sensitivity indicated that M1 and M0 were the most sensitive, while M3 and M7 were poorly sensitive and M4-M5 were confirmed to have a moderate sensitivity (35). Although no correlation was made between ASNase sensitivity and ASNS protein expression in that paper, a good response to therapy associated with low ASNS mRNA expression was later reported, at least for M0 (36). More recently, since chromosome 7 monosomy (-7) is frequently detected in adverse-risk AML and therapy-related myeloid neoplasms in children, the hypothesis that this aberration correlates with sensitivity to ASNase was investigated (37).…”
Section: Low Expression Of Asns As a Marker Of Sensitivity To Asnase mentioning
confidence: 95%
“…Generally, asparaginase may be beneficial for malignancies expressing low or no ASNS activity (68,70,73,74), and several studies have investigated the use of asparaginase in non-hematologic malignancies, such as pancreatic, ovarian, and breast cancers (75)(76)(77)(78)(79). Furthermore, there is substantial clinical evidence that including asparaginase during the treatment of AML results in better treatment outcomes (80)(81)(82)(83)(84)(85)(86)(87). While few studies in CML patients are available to assess the clinical efficacy of asparaginase (88)(89)(90)(91), preclinical studies indicate that asparaginase may also be beneficial for CML treatment (92,93).…”
Section: There Is Strong Clinical Evidence Supporting Vulnerabilities To Aspartate-derived Neaas In Leukemiasmentioning
confidence: 99%
“…Vincristine (VCR) is a widely used chemotherapeutic agent for the treatment of acute leukemia and solid tumors, but not acute myeloid leukaemia (132). It has been hypothesized that resistance of myeloblasts to VCR is related to MPO and production of HOCl.…”
Section: Taurinementioning
confidence: 99%